PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE EVERYONE IS A TEACHER HERE (ETH) DISERTAI SPEED TEST TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMP NEGERI 2 PAINAN - Deswinda, Nadia; Aima, Zulfitri; Mardiyah, Ainil (STKIP PGRI Sumbar, 2014)
Â The research are motivated by the mathematics conceptual understanding of the students that still low. The aim of this research to determine whether the mathtematics conceptual understanding of the students taught by using active learning strategy type Everyone is a Teacher Here (ETH) accompanied Speed Test was better than that of students tought by using conventional learning. This was an experimental research. The population of the research was the students in class VIII SMPN 2 Painan. The instrument of research was an essay posttest whose reliability was 0.83. The result hypothesis test using MINITAB software obtained P-value = 0.001 was less than Î± = 0.05. It can be concluded that the mathematics conceptual understanding of the students tought by using active learning strategy type Everyone is a Teacher Here (ETH) accompanied Speed Test was better than that of students tought by using conventional learning in class VIII SMPN 2 Painan.Â